In Vitro formation and characterization of the skeletal muscle α·β Tropomyosin heterodimers - Kalyva, Athanasia (2012)
Tropomyosin (Tm) is a dimer made of two alpha helical chains associated into a parallel coiled-coil. In mammalian skeletal and cardiac muscle the Tm is expressed from two separate genes to give the α- and β-Tm isoforms. These associate in vivo to form homo (α(2)) and heterodimers (α·β) with little β(2) normally observed. The proportion of α(2) vs α·β varies across species and across muscle types from almost 100 % α(2)- to 50 % α·β-Tm. The ratio can also vary during development and in disease. The functional significance of the presence of these two isoforms has not been defined because it is difficult to isolate or purify the α·β dimer for functional studies. Here we report an effective method for purifying bacterially expressed Tm as α·β dimers using a cleavable N-terminal tag on one of the two chains. The same method can be used to isolate Tm dimers in which one chain carries a mutation. We go on to show that the α·β dimers differ in key properties (actin affinity, thermal stability) from either the α(2)- or β(2)-Tm. However, the ability to regulate myosin binding when combined with cardiac troponin appears unaffected.